Eficácia do tratamento da terapia de voz para pólipos na prega vocal e fatores preditivos de sua eficácia - Silva, Joice Maely Souza da; Gomes, Adriana de Oliveira Camargo; Oliveira, Kelly Greyce Sukar Cavalcanti de; Lira, Zulina Souza de (Distúrbios da Comunicação, 2018)
Yoon Se Lee, et al. Treatment efficacy of voice therapy for vocal fold polyps and factors predictive of its efficacy. Journal of Voice. Jan, 2017; 31 (1): 129-133.